Different positions in society, differing views of the world: the privatization of water and sanitation services in Minas Gerais, Brazil - Neves-Silva, Priscila; Braga, Juliana Gontijo; Heller, Léo (Frontiers in Sustainable Cities, 2023)
Introduction: In 2020, the Brazilian government sanctioned the Law No. 14.026, which established new guidelines for water and sanitation in the country and encourages service privatization. Based on this, the government of the State of Minas Gerais, in Brazil, have proposed a bill for these services. Regarding this bill, different social actors in the state of Minas Gerais have expressed different assessment about the outcomes of the management model proposed and its impact in the realization of the human rights to water and sanitation. Methods: We used content analysis to assess the position of different actors – government, civil society and private sector - in 3 public events that were recorded and posted at the YouTube platform. Results: The analyses suggest that the positions of the current government is aligned with those of the private sector and that they agree that privatization can lead to the universalization of access. These actors did not mention the human rights to water and sanitation in their discourses. Civil society organizations are concerned about the guarantee of those rights. For them, privatization can refrain the access of population in vulnerable populations and poor municipalities, due to increases in tarifas. Discussion: The discourses about water and sanitation privatization as an instrument to reach the universalization is in dispute. Private sector actors and government representatives, aligned with the neoliberal agenda, support the privatization. Civil society organizations defend the improvement of public management as the path to universalization. Representatives of municipalities were not included in the discussion for the new bill. The different positions in society relate the different views this actors have about privatization and of the world.